Molecularly Imprinted High Affinity Nanoparticles for 4-Ethylphenol Sensing. (2015) - Garcia-Mutio, D.; Guerreiro, A.; Gomez-Caballero, A.; Gutierrez-Climente, R.; Piletsky, S.; Goicolea, M.A.; Barrio, R.J.
Abstract: A novel sensor for 4-ethylphenol (4EP) was developed based on molecularly imprinted nanoparticles produced via the solid phase imprinting method. The nanoparticles were immobilised on the surface of a gold electrode previously modified with a self assembled monolayer of lipoic acid coupled to EDC/NHS ((1-ethyl-3-[dimethylaminopropyl]carbodiimide)/N-hydroxysuccinimide). Each step of the process was characterised by electrochemical impedance spectroscopy and cyclic voltammetry. The electrode was used to selectively determine 4EP by differential pulse voltammetry; a quite remarkable sensitivity improvement was observed in the nanoparticle-modified electrode in reference to the non modified bare gold electrode.